2014
DOI: 10.1007/s00216-014-8060-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel and rapid HPGPC-based strategy for quality control of saccharide-dominant herbal materials: Dendrobium officinale, a case study

Abstract: Qualitative and quantitative characterization of natural saccharides, especially polysaccharides, in herb materials remains a challenge due to their complicated structures and high macromolecular masses. Currently available methods involve time-consuming and complicated operations, and present poor specificity. Here, a novel and rapid high-performance gel permeation chromatography (HPGPC)-based approach is described for quality assessment of saccharide-dominant herbal materials by simultaneous qualitative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…2a-d. The HPMs were consistently detected at 25.56 ± 1.48 min, which was in agreement with the previous study [21]. In Fig.…”
Section: Chemical Characterization and Content Determination Of Hpms supporting
confidence: 93%
See 3 more Smart Citations
“…2a-d. The HPMs were consistently detected at 25.56 ± 1.48 min, which was in agreement with the previous study [21]. In Fig.…”
Section: Chemical Characterization and Content Determination Of Hpms supporting
confidence: 93%
“…Deionized water was prepared by Millipore Milli Q-Plus system (Bedford, MA, USA). HPM for chemical characterization was isolated in our laboratory as described previously [21].…”
Section: Chemicals Reagents and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the methanolic extract exhibited a pleiotropic effect on obesity-induced parameters and exerted a renoprotective effect in high-fat diet-fed mice [8]. Polysaccharides and phenols are the main constituents identified in D. officinale [9]. Therefore, it was hypothesized that the antilipase agents might exist in the plant.…”
Section: Introductionmentioning
confidence: 98%